Secured Crypto Stegano Data Hiding Using Least Significant Bit Substitution and Encryption - Shakya, Subarna; Lamichhane, Sanjita (Journal of Advanced College of Engineering and Management, 2016)
Information Exchange has always been an integral part of our lives. With the rapid advancement in Information and communication technologies, communication and information exchange have become much easier and faster but at the same time the issues regarding security of data and its confidentiality have become our major concern. Cryptography and Steganography are two such data hiding techniques that can be combined together in order to enhance data security. Cryptography scrambles a message so that it cannot be understood whereas Steganography hides its existence. In this process, message is first encrypted using an algorithm based on Fibonacci series or the Rijndael cryptographic algorithm and then the encrypted message is embedded inside an image using improved Least Significant Bit substitution method where the secret information is stored into a specific position of Least Significant Bit of an image based on the security key entered. This combinational methodology will satisfy the requirements such as capacity, security and robustness for secure data transmission over an open channel. Journal of Advanced College of Engineering and Management, Vol. 2, 2016, Page: 105-112